2005
DOI: 10.1080/08880010500278780
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Relapsed Multifocal Nonvisceral Infantile Myofibromatosis

Abstract: Infantile myofibromatosis is a very rare tumor in childhood and infancy. The authors report on a 4-year-old boy who presented with two relapses of initially multifocal infantile myofibromatosis without visceral involvement. The lesions of the skull and the abdomen were excised while osteolytic lesions of the limbs were not treated. Chemotherapy or radiation have not been applicated. Three years after initial diagnosis there is no evidence for persistence or recurrence of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Myofibromatosis with visceral involvement results in death in about 70% of patients. Chemotherapy or interferon may be effective in some cases [161][162][163][164].…”
Section: Infantile Myofibromatosismentioning
confidence: 99%
“…Myofibromatosis with visceral involvement results in death in about 70% of patients. Chemotherapy or interferon may be effective in some cases [161][162][163][164].…”
Section: Infantile Myofibromatosismentioning
confidence: 99%
“…Recurrent IM is rare and it has been reported in 17 patients in the literature (Table 3). 14,26,[34][35][36][37][38][39][40][41] Noteworthy is the high recurrence received chemotherapy of various combinations 34,38 or spontaneously regressed. 14,41 As demonstrated by our Patient 2, recurrence can be treated with the same chemotherapeutic regimen used for the treatment of the initial disease.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Recurrent IM is rare and it has been reported in 17 patients in the literature (Table 3). 14,26,34–41 Noteworthy is the high recurrence rate reported by Beck et al in a series of head and neck lesions 34 . This high rate of recurrence reflects an unfavorable location of tumors that were only subtotally resected and needed further surgical intervention when they regrew.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In a more recent review, Levine et al summarized 30 cases of multicentric IM with or without visceral involvement 6 . Review of these cases revealed only 1 in which involvement was only osseous; all others cases had lesions that involved skin and soft tissue or organs 20 .…”
Section: Discussionmentioning
confidence: 99%